THE INFLUENCE OF NURSING MANAGEMENT AND LEADERSHIP ON NURSES ' JOB SATISFACTION AT SUNDARI HOSPITAL MEDAN - Suherni, (Mitra Husada Health Internasional Conference (MIHHICo), 2026)
Background: Nurse job satisfaction is an important indicator in determining the quality of nursing services. However, various studies show that nurse job satisfaction in Indonesia remains a challenge. Objectives: This study aims to analyze the influence of management and leadership on nurses' job satisfaction. Methods: The study employed a cross-sectional quantitative design, involving 88 nurse respondents at Sundari Hospital, Medan. The sample was selected using proportional stratified random sampling. Data collection used three structured questionnaires that had been tested for validity and reliability. Data analysis was performed univariately, bivariately using the Chi-square test, and multivariately using binary logistic regression. Results: The majority of respondents rated nursing management as good (70.5%) and leadership as good (64.8%), and reported high job satisfaction (64.8%). The Chi-square test showed a significant relationship between nursing management and job satisfaction (p=0.001), and leadership as good (p=0.001) with job satisfaction (p=0.001). The results of binary logistic regression confirmed that nursing management is the most dominant predictor, with an Odds Ratio (OR) of 6.632 (95% CI: 2.432-18.087), compared to leadership, with an OR of 4.768 (95% CI: 1.796-12.656), with a Nagelkerke R Square value of 0.412. Conclusions: This study found that nursing management and leadership are key determinants in nurse job satisfaction, with nursing management the most dominant variable. It is recommended that improving the quality of nursing management through appropriate workforce planning and fair shift scheduling be prioritized to improve nurse job satisfaction.